2019
DOI: 10.1038/s41598-019-44793-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology, pathogenicity, and structural analysis of haemoglobin variants in the Yunnan province population of Southwestern China

Abstract: Abnormal haemoglobin (Hb) variants result in the most commonly inherited disorders in humans worldwide. In this study, we investigated the molecular epidemiology characteristics of Hb variants, along with associated structural and functional predictions in the Yunnan province population of Southwestern China. A total of 41,933 subjects who sought haemoglobinopathy screening were included. Based on bioinformatics and structural analysis, as well as protein modeling, the pathogenesis and type of Hb genetic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The most common mutation was CD41/42 (‐TCTT), which was consistent with data from Guangdong and several nearby provinces 6,12,13,21,22 . In other provinces, such as Hunan, Yunnan and Fujian, IVS‐II‐654 (C>T) was the most common mutation, whilst CD41/42 (‐TCTT) was the second most common 23,24,25 . These studies indicated that the common and widespread mutations were similar across southern China, with diverse frequencies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most common mutation was CD41/42 (‐TCTT), which was consistent with data from Guangdong and several nearby provinces 6,12,13,21,22 . In other provinces, such as Hunan, Yunnan and Fujian, IVS‐II‐654 (C>T) was the most common mutation, whilst CD41/42 (‐TCTT) was the second most common 23,24,25 . These studies indicated that the common and widespread mutations were similar across southern China, with diverse frequencies.…”
Section: Discussionsupporting
confidence: 83%
“…6,12,13,21,22 In other provinces, such as Hunan, Yunnan and Fujian, IVS-II-654 (C>T) was the most common mutation, whilst CD41/42 (-TCTT) was the second most common. 23,24,25 These studies indicated that the common and widespread mutations were similar across southern China, with diverse frequencies. The different distribution of β-globin mutations, across different geographical locations, reflects the heterogeneity of β-thalassemia.…”
Section: Hematological Parameters In Thalassemia Carriers Of Differen...mentioning
confidence: 95%
“…According to the Iranome database, the HBD: c.394C>G variant has been observed in a Kurdish healthy individual in heterozygous form. Since the only report of this variant in the literature is related to Zhang et al's [21] study, it can be assumed that the present study is the second one to report this variant in the world and the first study to annotate it in Iran.…”
Section: Discussionmentioning
confidence: 84%
“…Zhang et al [21] reported p.Gln132Glu (HBD: c.394C>G) as a novel δ-globin variant in a healthy Chinese 35-year-old man in 2019 and named it Hb A2-Puer. The hematological and electrophoretic data related to this Hb variant in heterozygous state were as follows: Hb (g/dL) 16.1, MCV (fL) 85.2, MCH (pg) 29.0, Hb A (%) 97.4, Hb A 2 (%) 1.3, and Hb X (%) 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…The thalassaemias are characterised by absent or decreased production of normal haemoglobin. Whereas, the Hb variants are characterised by structural protein abnormalities in the globin chains, including α-globins, β-globins, δ-globins and γ-globins 3. To date, more than 1800 entries of variants have been registered in the Globin Gene Server, Hb var database 4.…”
Section: Introductionmentioning
confidence: 99%